2010
DOI: 10.1002/mrm.22328
|View full text |Cite
|
Sign up to set email alerts
|

Automatic temperature control for MR-guided interstitial ultrasound ablation in liver using a percutaneous applicator: Ex vivo and in vivo initial studies

Abstract: Image-guided thermal ablation offers minimally invasive options for treating hepatocellular carcinoma and colorectal metastases in liver. Here, the feasibility and the potential benefit of active temperature control for MR-guided percutaneous ultrasound ablation was investigated in pig liver. An MR-compatible interstitial ultrasound applicator (flat transducer), a positioning system with rotation-translation guiding frame, and an orbital ring holder were developed.Step-by-step rotated elementary lesions were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Moreover, such an implantable US device must only minimally interfere with MRI in patients who require repeated MRI to monitor their treatment. Other authors have shown that implantable US devices could be safely used with MRI, 4 and in our case, preliminary tests have shown that our device is also MRI compatible.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, such an implantable US device must only minimally interfere with MRI in patients who require repeated MRI to monitor their treatment. Other authors have shown that implantable US devices could be safely used with MRI, 4 and in our case, preliminary tests have shown that our device is also MRI compatible.…”
Section: Discussionsupporting
confidence: 65%
“…Proton resonance frequency shift (PRFS)-based MR thermometry (Delabrousse et al, 2010) was used on a 3-T clinical scanner (Siemens Magnetom Trio 3T TIM System, Erlangen, Germany) in order to determine the heat transfer time constant in cartilage. We performed MRI acquisitions on the right knee of four male subjects (age¼30.373.8 yr) using a CP Transmit/receive head coil with integrated preamplifier and 16 rungs (Siemens AG, Erlangen, Germany).…”
Section: Time Constant Of Cartilage Heat Transfer Obtained By Magnetimentioning
confidence: 99%
“…These devices have diameters ranging from 3 to 10 mm and operate at frequencies of 3-10 MHz. Interstitial therapeutic ultrasound applicators in particular have been built and tested using a variety of designs by several different groups and include single-element 19,20 and multi-element designs with planar 21-24 and cylindrical 18,25 elements.…”
Section: Introductionmentioning
confidence: 99%